Pop idols, mediatized places and identity-oriented performances of fans as domestic tourists in Japan - Mandujano Salazar, Yunuen Ysela (Routledge, 2020)
This chapter discusses the ways in which the media activities of the Japanese idol group Arashi and their explicit and implicit promotion of services and products anchored to specific spaces in Japan have re-signified certain places for audience. It aims to show that a special segment of domestic tourists is created and, influenced by media representations, they make sense of and perform in different ways than other visitors in mediatized places. Documental and interpretative textual analysis of media contents were used to understand the insertion of Arashi in strategies for the promotion of national tourism.